The Excretion Period of Triclabendazole Residual and it's Metabolites after Triclafascid Application on Sheep - M. B. Musaev; I. E. Shumakovich; M. S. Khalikov; N. B. Emelyanova; P. P. Kochetkov; N. E. Patyukov; V. E. Abramov (Российский паразитологический журнал)
The purpose of the research: studying the excretion period of triclabendazole residual and its metabolites after triclafascid application on productive animals. Materials and methods. Researches were carried out on 12 sheep of Romanov breed at the age of 1 year. The animals selected in the experiment were divided according to the principle of analogues into 4 groups (control and 3 experimental) for 3 animals in every slaughter period. Triclafascid was administered to the sheep of the three experimental groups on a single occasion at a therapeutic dose of 2.0 mg/kg under active ingredient (20 mg/kg of preparation) orally individually in the form of an aqueous solution by means of rubber bottle; control animals did not take a preparation. Initially, the sheep of the control group were slaughtered, and then experimental sheep were slaughtered after the application of triclafascid at 7, 14 and 21 days. Liver, kidneys, muscle tissue, heart, lungs and skin with subcutaneous fat were collected for the research. Triclabendazole content and its metabolites was determined by high performance liquid chromatography method (HPLC) with fluorometric detection. Analytes determination was performed on Agilent 1260 liquid chromatograph (USA) with a column for reverse phase HPLC Kromasil-100-3.5-C18 and a pre-column Phenomenex C18. Results and discussion. After animals dehelminthization with triclafascid at a therapeutic dose of 2.0 mg/kg, no drug residual and its metabolites were detected in muscles, fat, lungs, spleen, kidneys on the 7th day. Traces remain in all animals in the liver after 14 days. Residual amounts of triclabendazole-sulfoxide and sulfone were not found in the tissues on the 21st day of the experiment. Animals slaughtering for household needs and using of forcibly killed animals’ meat for food can be allowed after 15 days after dehelminthization.